La pedagogía de los abuelos de la comunidad de Cañicapac” - Japón Gualán, Delia Getrudiz. (2013)
The human being needs a subject. It has always been based on the search of learning through pedagogy. Pedagogy emerged from the life experience of grandparents who have passed on orally and through structured practice Saraguro village life. In this research work, we intend to somehow demonstrate the different ways of looking at life, its culture and particularly, the wisdom and knowledge that have saved Grandparents and these are part of a community heritage Cañicapac, which aims to contribute to the construction of an alternative proposal within the educational work for Cañicapac community. We start from the analysis of the geographical, social, cultural and economic development of the community, and then turn to summarize those knowledges that are in people who have had the opportunity to talk with them, in the final chapters, we try to show on the construction of a theoretical methodology for learning processes in schools, as well as experiences from students who applied this knowledge in the academic learning process. Finally, with this paper, we contribute to strengthening the quality of education for intercultural communities Saraguro people